2019
DOI: 10.1534/genetics.119.302191
|View full text |Cite
|
Sign up to set email alerts
|

The TOR Pathway Plays Pleiotropic Roles in Growth and Stress Responses of the Fungal Pathogen Cryptococcus neoformans

Abstract: The target of rapamycin (TOR) pathway is an evolutionarily conserved signal transduction system that governs a plethora of eukaryotic biological processes, but its role in Cryptococcus neoformans remains elusive. In this study, we investigated the TOR pathway by functionally characterizing two Tor-like kinases, Tor1 and Tlk1, in C. neoformans. We successfully deleted TLK1, but not TOR1. TLK1 deletion did not result in any evident in vitro phenotypes, suggesting that Tlk1 is dispensable for the growth of C. neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…neoformans is confronted with a variety of host-specific stresses, such as nutrient limitation, temperature shift, changes in oxygen/carbon dioxide levels, oxidative/nitrosative stress, and osmotic stress, upon its infection of the host lung. Signaling pathways or factors involved in the stress response have been identified and extensively studied [56,97,98]. ZNFs are also involved in the regulation of the stress response in C. neoformans.…”
Section: Znfs Regulate Stress Resistance In C Neoformansmentioning
confidence: 99%
“…neoformans is confronted with a variety of host-specific stresses, such as nutrient limitation, temperature shift, changes in oxygen/carbon dioxide levels, oxidative/nitrosative stress, and osmotic stress, upon its infection of the host lung. Signaling pathways or factors involved in the stress response have been identified and extensively studied [56,97,98]. ZNFs are also involved in the regulation of the stress response in C. neoformans.…”
Section: Znfs Regulate Stress Resistance In C Neoformansmentioning
confidence: 99%
“…Similar to this past study, we also identified pleiotropic QTGs contributing to more than one virulence-related trait examined here (including thermal tolerance and melanization), namely the genes RIC8 and SSK2. While our study did not share any of the previously implicated QTGs (Lin et al, 2006;Vogan et al, 2016), across several studies -not just those using QTL mapping strategies -observing pleiotropic effects of genes and pathways connected to virulence and virulence-associated traits seems to be a unifying phenomena (Shen et al, 2010;Fang et al, 2012;Tefsen et al, 2014;Lendenmann et al, 2015;Cavalheiro et al, 2018;So et al, 2019;Lev et al, 2019).…”
Section: Comparison To Previous Qtl Studies In Cryptococcus and Othermentioning
confidence: 61%
“…Although the TOR pathway is a highly conserved mechanism across eukaryotes, its role in C. neoformans is a topic of debate (So et al, 2019). Researchers have found two Tor-like kinases, Tor1 and Tlk1, in C. neoformans (So et al, 2019).…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…This study discovered that TLK1 is a dispensable gene resulting in the cultivation of a viable strain following its deletion. The opposite was concluded when TOR1 was deleted (So et al, 2019). Further research explored the function of Tor1 by creating strains that overexpress the TOR1 gene (So et al, 2019).…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
See 1 more Smart Citation